Influence of polymorphisms in TNF-α and IL1β on susceptibility to alcohol induced liver diseases and therapeutic potential of miR-124-3p impeding TNF-α/IL1β mediated multi-cellular signaling in liver microenvironment - Dasgupta, Debanjali; Ghosh, Suchandrima; Dey, Indrashish; Majumdar, Swagata; Chowdhury, Saheli; Das, Subhas; Banerjee, Sanjana; Saha, Mehelana; Ghosh, Amit; Roy, Neelanjana; Manna, Alak; Ray, Sukanta; et al. (Frontiers in Immunology, 2023)
Background Alcoholic liver disease (ALD) is the leading cause of liver cirrhosis-related death worldwide. Excessive alcohol consumption results in enhanced gut permeability which triggers sensitization of inflammatory cells to bacterial endotoxins and induces secretion of cytokines/chemokines leading to activation of stellate cells/neutrophil infiltration/hepatocyte injury followed by steatohepatitis/fibrosis/cirrhosis. However, all chronic alcoholics do not develop ALD. This study investigated the causes of differential immune responses among ALD patients and alcoholic controls (ALC) to identify risk factors and assess the therapeutic potential of miR-124-3p. Materials and Methods: Bio-Plex ProTM Human Chemokine analysis/qRT-PCR array was used for the identification of deregulated immune genes. Sequencing/luciferase assay/ELISA detected the polymorphisms. THP1 co-cultured with HepG2/LX2/HUVEC and apoptosis assay/qRT-PCR/neutrophil migration assay was employed as required. Results: The combined data analysis of the GSE143318/Bio-Plex ProTM Human Chemokine and qRT-PCR array revealed that six genes (TNFα/IL1/IL8/MCP1/IL6/TGFβ) were commonly overexpressed in both serum/liver tissue of ALD patients compared to ALC. The promoter sequence analysis of these 6 genes among ALD (n=322)/ALC (n=168) samples revealed that only SNPs, rs361525(G/A) at -238 in TNF-α and rs1143627(C/T) at -31 in IL1β were independently associated with ALD respectively. To evaluate the functional implication of these SNPs on ALD development, the serum level of TNF-α/IL1β was verified and observed significantly higher level in ALD patients with risk genotype TNF-αGA/IL1βCT+TT than TNF-αGG/IL1βCC. The TNF-α/IL1β promoter Luciferase-reporter assays showed significantly elevated levels of luciferase activities with risk genotypes AA/TT than GG/CC respectively. Furthermore, treatment of conditioned medium of TNF-α/IL1β over-expressed THP1 cells to HepG2/LX2/HUVEC cells independently showed enhanced levels of ER stress/apoptosis in HepG2/increased TGFβ and collagen-I production by LX2/huge neutrophil infiltration through the endothelial layer. However, restoration of miR-124-3p in THP1 attenuated such intercellular communications and hepatocyte damage/collagen production/neutrophil infiltration. Target analysis and luciferase-reporter assays revealed that both TNF-α/IL1β were inhibited by miR-124-3p along with multiple genes from TLR4 signaling pathways/apoptosis/fibrogenesis pathways including MYD88, TRAF3/TRADD, Caspase8/PDGFRA, TGFβR2/MCP1, ICAM1 respectively. Conclusions: Thus, rs361525(G/A) in TNF-α and rs1143627(C/T) in IL1β gene may be used as early predictors of ALD. Impeding overexpressed TNF-α/IL1β and various genes from associated immune response pathways, miR-124-3p exhibits robust therapeutic potential for ALD patients.